Continuous monitoring of suspended sediment concentrations using image analytics and deriving inherent correlations by machine learning - Mohammad Ali Ghorbani; Rahman Khatibi; Vijay P. Singh; Ercan Kahya; Heikki Ruskeepää; Mandeep Kaur Saggi; Bellie Sivakumar; Sungwon Kim; Farzin Salmasi; Mahsa Hasanpour Kashani; Saeed Samadianfard; Mahmood Shahabi; et al. (NATURE PUBLISHING GROUP, 2025)
The barriers for the development of continuous monitoring of Suspended Sediment Concentration (SSC) in channels/rivers include costs and technological gaps but this paper shows that a solution is feasible by: (i) using readily available high-resolution images; (ii) transforming the images into image analytics to form a modelling dataset; and (iii) constructing predictive models by learning inherent correlation between observed SSC values and their image analytics. High-resolution images were taken of water containing a series of SSC values using an exploratory flume. Machine learning is processed by dividing the dataset into training and testing sets and the paper uses the following models: Generalized Linear Machine (GLM) and Distributed Random Forest (DRF). Results show that each model is capable of reliable predictions but the errors at higher SSC are not fully explained by modelling alone. Here we offer sufficient evidence for the feasibility of a continuous SSC monitoring capability in channels before the next phase of the study with the goal of producing practice guidelines.